2016
DOI: 10.1016/j.rbmo.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peri-implantation administration of uterine relaxing agents in assisted reproduction treatment cycles: a systematic review and meta-analysis

Abstract: Sub-endometrial junctional zone peristalsis is increased by ovarian stimulation and traumatic embryo transfer, and is linked with decreased implantation and pregnancy rates in assisted reproduction treatments. Various agents have been used to inhibit uterine hyper-peristalsis at the time of embryo transfer with conflicting results. This systematic review aimed to identify if uterine relaxants administered in the peri-implantation period during assisted reproduction treatments could improve pregnancy outcomes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The higher rate of caesarean sections may be partially related to the higher rate of complications in the obese/overweight women, however, there is data to suggest that this difference is not completely explained by the high-risk obesity-associated conditions alone [26]. High caesarean section rates have been documented in otherwise low-risk obese/overweight women, and it is therefore plausible that being obese/overweight itself is an independent risk factor for labor dystocia, resulting in increased caesarean section [2729].…”
Section: Discussionmentioning
confidence: 99%
“…The higher rate of caesarean sections may be partially related to the higher rate of complications in the obese/overweight women, however, there is data to suggest that this difference is not completely explained by the high-risk obesity-associated conditions alone [26]. High caesarean section rates have been documented in otherwise low-risk obese/overweight women, and it is therefore plausible that being obese/overweight itself is an independent risk factor for labor dystocia, resulting in increased caesarean section [2729].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that difficult embryo transfer stimulates uterine contractions and this has been postulated to lead to non-adherence of the embryo(s) to the endometrium, expulsion of the embryos from the uterine cavity shortly after embryo transfer, or both [50]. The same finding has been reported in a small study in natural cycles [51].…”
Section: Accepted Manuscriptmentioning
confidence: 55%
“…Another meta-analysis attempting at reducing subendoemtrial contractility at time of ET to increase pregnancy rates didn't show any benefit using various agents (48) In the latest report by the ICMART [21] including data from the years 2008-2010, single embryo transfer (SET) increased from 25.7% to 30% with a resulting drop in Multiple twin births to 19.6% & the triplets to 1.0%. Individual European countries with strict single embryo transfer policies such as Sweden have 76.9% of their transfers SET and a resulting 5.4 % only twin births [49].…”
Section: Discussionmentioning
confidence: 99%